QXMD: An open-source program for nonadiabatic quantum molecular dynamics - Fuyuki Shimojo; Shogo Fukushima; Hiroyuki Kumazoe; Masaaki Misawa; Satoshi Ohmura; Pankaj Rajak; Kohei Shimamura; Lindsay Bassman; Subodh Tiwari; Rajiv K. Kalia; Aiichiro Nakano; Priya Vashishta (SoftwareX, 2019)
QXMD is a scalable, parallel program for Quantum Molecular Dynamics simulations with various eXtensions. Its simulation engine is based on (time-dependent) density functional theory using pseudopotentials and a plane-wave basis set, while extensions include nonadiabatic electron–nuclei dynamics and multiscale shock technique. QXMD serves as a community-development platform for new methods and algorithms, a research platform on high-end parallel supercomputers, and an educational platform for hands-on training. Keywords: Nonadiabatic quantum molecular dynamics, Parallel computing, Hands-on training